Extremal Inverse Eigenvalue Problem for a Special Kind of Matrices - Zhibing Liu; Yeying Xu; Kanmin Wang; Chengfeng Xu (Journal of Applied Mathematics)
We consider the following inverse eigenvalue problem: to construct a special kind of matrix (real symmetric doubly arrow matrix) from the minimal and maximal eigenvalues of all its leading principal submatrices. The necessary and sufficient condition for the solvability of the problem is derived. Our results are constructive and they generate algorithmic procedures to construct such matrices.